2011
DOI: 10.1055/s-0030-1268466
|View full text |Cite
|
Sign up to set email alerts
|

Apelin Serum Levels are not Associated with Early Atherosclerosis or Fat Distribution in Young Subjects with Increased Risk for Type 2 Diabetes

Abstract: Apelin is proposed to possess protective cardiovascular properties and may furthermore promote favorable effects on glucose metabolism. First data in humans seem to support this hypothesis. Therefore we aimed to assess the meaning of apelin as an early risk indicator in young subjects prone to atherosclerosis and type 2 diabetes. Furthermore we examined the association of apelin serum levels with insulin sensitivity/resistance and body fat distribution as probably dependent cardiovascular risk factors. We exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
0
12
1
Order By: Relevance
“…In contrast, Rittig et al. (2011) [19] have recently documented the absence of relationship between early carotid atherosclerosis and apelin levels in young individuals with increased risk of type 2 diabetes. Compared to that study, we enrolled patients with advanced carotid atherosclerosis and multiple cardiovascular risk factors, which could explain the above divergent results.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Rittig et al. (2011) [19] have recently documented the absence of relationship between early carotid atherosclerosis and apelin levels in young individuals with increased risk of type 2 diabetes. Compared to that study, we enrolled patients with advanced carotid atherosclerosis and multiple cardiovascular risk factors, which could explain the above divergent results.…”
Section: Discussionmentioning
confidence: 99%
“…However from a pathophysiological point of view, some conflicting data have been reported. For example, Rittig et al [166] observed that plasma apelin levels are not associated with early stages of atherosclerosis in young subjects prone to atherosclerosis and type 2 diabetes. Interestingly, other studies in animal models suggested a role of apelin-APJ system in vasculature oxidative stress.…”
Section: Apelinmentioning
confidence: 99%
“…Rittig et al [3] found that serum apelin-36 levels were not associated with early AS using apelin-36 as an early risk indicator in young subjects prone to AS. However, plasma apelin levels were lower in patients with elevated low-density lipoprotein-cholesterol (LDL-C) compared with healthy controls [4].…”
Section: Expression and Location Of Apelin/apj In Atherosclerosis Patmentioning
confidence: 99%